An Optimization Design of Collimator in The Thermal Column of Kartini Reactor For BNCT - M. Ibnu Khaldun; Andang Widi Harto; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2017)
Studies were carried out to design a collimator which results in epithermal neutron beam for in vivo experiment of Boron Neutron Capture Therapy (BNCT) at the Kartini Research Reactor by means of Monte Carlo N-Particle (MCNP) codes. Reactor within 100 kW of thermal power was used as the neutron source. All materials used were varied in size, according to the value of mean free path for each material. MCNP simulations indicated that by using 6 cm thick of Natural Nickel as collimator wall, 65 cm thick of Al as moderator, 3 cm thick of Ni-60 as filter, 6 cm thick of Bi as γ-ray shielding, 3.5 cm thick of Li2CO3-polyethilene, with 2 cm aperture diameter. Epithermal neutron beam with maximum flux of 6.60 x 108n.cm-2.s-1 could be produced. The beam has minimum fast neutron and γ-ray components of, respectively, 1.82 x 10-13Gy.cm2.n-1 and 1.70 x 10-13 Gy.cm2.n-1, minimum thermal neutron per epithermal neutron ratio of 0.041, and maximum directionality of 2,12. It did not fully pass the IAEA’s criteria, since the epithermal neutron flux was below the recommended value, 1.0 x 109 n.cm-2.s-1. Nonetheless, it was still usable with epithermal neutron flux exceeding 5.0 x 108 n.cm-2.s-1. it is still feasible for BNCT in vivo experiment.